Coupled Analysis of Heat Transfer in a Molten Pool With Three-Layer Configuration - Deng, Jian; Zhu, Dahuan; Luo, Yuejian; Sun, Hongping; Zhang, Ming; Liu, Lili; Xiang, Qingan; Wu, Xiaoli; Xu, Youyou; Xiong, Qingwen (Frontiers in Energy Research, 2022)
Understanding a reliable description of the heat transfer in the molten pool with three-layer configuration is inevitable for the design of severe accident mitigation measures in research reactors, such as IVR-ERVC. However, investigations on a thick lower metallic layer are scarce. Thus, further studies on heat transfer in a molten pool with a thick lower metallic layer are highly required, based on previous severe accident studies in light water reactors. This study conducts a numerical simulation of heat transfer in the molten pool with a thick lower metallic layer during a severe accident, combining model development, code verification, and code application. First, the MPCAP code has been developed, based on the coupled simulation of natural convection inside the molten pool, two-dimensional heat conduction in the RPV lower head, and convection outside the reactor vessel wall. Then, a verification case has been conducted using three-layer configuration in AP1000. The AP1000 verification case indicates that the MPCAP code predicts important parameters in the molten pool well.